Activity patterns in process-aware information systems: basic concepts and empirical evidence. (11th August 2009) - Thom, Lucineia Heloisa; Reichert, Manfred; Iochpe, Cirano
Recently, a variety of workflow patterns have been suggested for capturing different aspects in process-aware information systems (PAISs), including control and data flow, resources, process change and exception handling. All these patterns are highly relevant for implementing PAISs and for designing process modelling languages. However, current patterns provide only a partial answer to the question of which business functions a designer might want to reuse when modelling processes. This paper presents a revised version of a collection of activity patterns to deal with this challenge. Each of them is related to a recurrent business function as it can be frequently found in process models (e.g., task execution request, notification, approval). We describe the identified activity patterns and their variants in detail. The main purpose of our paper is to discuss results from empirical studies in which we analysed more than 200 process models in order to evidence the practical relevance of the patterns. This includes a detailed analysis of the context in which activity patterns occur as well as the frequency of this occurrence. These empirical findings can be used for the design of more intelligent, pattern-based process modelling tools.